Bacterial Adhesion and Biofilm Formation of Enterococcus faecalis on Zwitterionic Methylmethacrylat and Polysulfones - Woitschach, Franziska; Kloss, Marlen; Schlodder, Karsten; Borck, Alexander; Grabow, Niels; Reisinger, Emil Christian; Sombetzki, Martina (Frontiers in Cellular and Infection Microbiology, 2022)
Biofilm-associated implant infections represent a major challenge for healthcare systems around the world due to high patient burden and enormous costs incurred. Enterococcus faecalis (E. faecalis) is the most prevalent enterococcal species identified in biofilm-associated infections. The steadily growing areas of application of implants demand a solution for the control of bacterial infections. Therefore, the development of modified anti-microbial implant materials and the testing of the behavior of different relevant bacterial strains towards them displays an indispensable task. Recently, we demonstrated an anti-microbial effect of zwitterionic modified silicone rubber (LSR) against Staphylococcus aureus. The aim of this study was to test another clinically relevant strain, E. faecalis on this new material in terms of bacterial colonization and biofilm formation of in comparison with two of the most commonly used thermoplastic polyurethanes (TPUs) and other modified LSR surfaces. By generating growth curves, crystal violet and fluorescence staining as well as analyzing the expression of biofilm associated genes, we demonstrated no anti-microbial activity of the investigated materials against E. faecalis. These results point to the fact that anti-microbial effects of novel implant materials do not always apply across the board to all bacterial strains.